2016
DOI: 10.1097/ico.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes After SMILE, LASEK, and LASEK Combined With Corneal Collagen Cross-Linking for High Myopic Correction

Abstract: SMILE, LASEK, and LASEK-CXL surgery appear to be safe and effective for high-degree myopic correction. However, the SMILE group had no haze and fewer induction of some higher-order aberrations compared with the LASEK and LASEK-CXL groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Small incision lenticule extraction (SMILE) and tPRK represent the newest developments in both lamellar and surface refractive surgery. Several studies have shown that both LASEK and SMILE are safe and effective surgical options, but SMILE is associated with fewer inductions of higher-order aberrations (HOAs) than LASEK (Yu et al 2015;Hyun et al 2017;Ganesh et al e1289 2018. In contrast, only a few studies have directly compared clinical outcomes, including visual acuity, refraction and HOAs, between SMILE and tPRK (Jun et al 2018;Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Small incision lenticule extraction (SMILE) and tPRK represent the newest developments in both lamellar and surface refractive surgery. Several studies have shown that both LASEK and SMILE are safe and effective surgical options, but SMILE is associated with fewer inductions of higher-order aberrations (HOAs) than LASEK (Yu et al 2015;Hyun et al 2017;Ganesh et al e1289 2018. In contrast, only a few studies have directly compared clinical outcomes, including visual acuity, refraction and HOAs, between SMILE and tPRK (Jun et al 2018;Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that LASEK combined with prophylactic corneal collagen cross-linking had less refractive change than LASEK alone but the difference was not statistically significant. [26] …”
Section: Discussionmentioning
confidence: 99%